If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + 22 = 64 Reorder the terms: 22 + 3x = 64 Solving 22 + 3x = 64 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-22' to each side of the equation. 22 + -22 + 3x = 64 + -22 Combine like terms: 22 + -22 = 0 0 + 3x = 64 + -22 3x = 64 + -22 Combine like terms: 64 + -22 = 42 3x = 42 Divide each side by '3'. x = 14 Simplifying x = 14
| y=7x+6 | | 122-2x=16x+22 | | 6+.8a=.9a | | 2p-6-6p=10-2p+4 | | 6+|5y+2|=9 | | -10+3x=26 | | 8x+4y=100 | | 5x-4=3(x+2) | | y=x^2+2x-8 | | 25+75=500 | | 5.5+(-1.4p)=-9.7 | | z-7-13=-2 | | -7=c-12 | | 3x+35=2x+62 | | 20y+3y=2y-50 | | x^2(-2x)-35=0 | | 3N+3=-6-9 | | 345-577x=356 | | ln(x+1)=1 | | ln(x-2)=0 | | (x^3)-(11x^2)+18x=0 | | x^2-5+6=0 | | 1-3(n+5)=-34 | | 4x+12=5x | | x-4=46 | | 4x+30=54 | | x+4=22 | | (x-5)+9=7 | | x^2+7x+23=0 | | x^2+2x=44 | | 3x+5=11x-2 | | (x*x)+12x=24 |